(untitled) (Environment & Health, 2020)
The negative effects of the harmful environmental factors on spermatogenesis are well known. Therefore, the immediate task is a bioindication of the environmental contamination with the reproductive toxicants. Objective: The purpose of the work is to study the indicators of spermatogenesis in the lake frog in a zone of the influence of the emissions from the Burshtyn thermal power plant. Materials and methods: Urinal sperm was taken from the male frogs collected near the individual building of Burshtyn and the industrial site of Burshtyn thermal power plant by means of the injection of surfagonat at a dose of 1.2µg /g bw. Such parameters as a spermatozoa concentration in sperm sample; a total amount of actively mobile forms; a percentage of spermatozoa with progressive motion were determined by the calculation in Goriaiev’s camera. To determine the number of live spermatozoa, we used Bloom’s staining of seminal fluid smear. Results: Although the average body weight of amphibians from the studied areas did not significantly differ from the control one, however, the weight of the testes, as well as its relation to the body weight and the volume of ejaculate demonstrated a tendency to a decrease in proportion to the gradient of technogenic load. Near the individual building of the city and the industrial site of the Burshtyn TPP, the volume of ejaculate in males decreases by 31% and 36%, respectively, and in the sperm sample, the sperm concentration is significantly reduced by 2.4 and 3.3 times in comparison with the control values. The number of dead spermatozoa increases to 25.69% and 31.20%, respectively, and the number of live forms decreases. At the same time, males from polluted areas had more spermatozoa with pathological changes of the head, main and intermediate parts of the flagellum. Under conditions of technogenic contamination, the total number of active spermatozoa is significantly reduced to 67.12%, including spermatozoa with progressive movement to 47.30%. Thus, the impact of the emissions from the Burshtyn thermal power plant has a pronounced reprotoxic effect and is manifested by depressive changes in spermatogenesis. The reproductive system of the lake frog is sensitive to the environmental pollution. Spermogram parameters are the informative biomarkers and can be used for the bioindication of the state of technogenically transformed territories.